COVID-19 related mortality profile at a tertiary care centre: a descriptive study - Bhandari, Sudhir; Sharma, Raman; Shaktawat, Ajit Singh; Banerjee, Subrata; Patel, Bhoopendra; Tak, Amit; Meena, Deepa; Agarwal, Abhishek; Gupta, Vishal; Sharma, Shrikant; Mahavar, Sunil; Chejara, Radhey Shyam; et al. (Scripta Medica, 2020)
Background/Aim: The recent pandemic of Severe Acute Respiratory Syndrome Corona Virus-2 (SARS-CoV-2) is yet another scourge from the coronaviridae family that causes illnesses ranging from common cold to more severe diseases such as Middle East respiratory syndrome (MERS-CoV) and severe acute respiratory syndrome (SARS-CoV). The numbers are still on the rise, despite a country wide lockdown and yet no definitive drugs and or/vaccines are available to manage the active COVID-19 cases.Methods: The present research design was a hospital based observational descriptive study conducted at S. M. S. Medical College and Attached hospitals, Jaipur, that analysed data of all the patients with COVID-19 related mortality, admitted between 1 April to 4 May 2020. Patients included in this study were RT-PCR confirmed cases of SARS-CoV-2 using nasopharyngeal and oropharyngeal swab samples.Results: The mean age of patients with COVID-19 related mortality was 53.41 ± 18.42 year with majority of patients belonging to age group of more than 60 years (41.18 %) followed closely by COVID-19 positive patients in age range of 45 to 60 years (33.33 %). The male to female ratio was 1.68: 1. Mean time lag between hospitalization and death reported was 6.18 days. Majority of the patients admitted (72.5 %) succumbed within 3 days of hospitalization. Eleven patients (21 %) were brought dead to the hospital who were tested COVID-19 positive after death. Most common comorbidity reported in patients with COVID-19 related mortality was hypertension (30 %) followed by diabetes mellitus (27.5 %).Conclusion: Hypertension and diabetes mellitus might be independent risk factors making an individual susceptible to COVID-19 related death. Elderly patients also have a greater risk of mortality. The non-availability of definitive management protocol and/or vaccine against COVID-19 makes public health preventive measures of social distancing, use of masks and frequent handwashing an important modality in the fight against COVID-19.
Keywords: age; comorbidity; COVID-19; hypertension; mortality